PENGARUH SARANA PRASARANA TERHADAP MINAT BELAJAR SISWA DI PONDOK PESANTREN AMIRUDDINIYAH DESA BANDAR TINGGI KECAMATAN BILAH HULU KABUPATEN LABUHANBATU SUMATERA UTARA - Wahyuni, Fitri Wahyuni Dm; Fauzi Ahmad Syawaluddin; Basyarul Ulya Nasution (Cahaya Ilmu Bangsa Institute, 2024)
Abstract The purpose of this study was to determine the effect of infrastructure on students' learning interests at the Amiruddiniyah Islamic Boarding School, Bandar Tinggi Village, Bilah Hulu District, Labuhanbatu Regency, North Sumatra. The method used is quantitative research. The population in the study were all grade IX students of the Amiruddiniyah Islamic Boarding School, the sample taken was 30 students. The data collection techniques used were observation, questionnaires, and documentation. The analysis method used was instrument validity testing, and instrument reliability testing. The results of the study obtained many respondents who argued that infrastructure had an effect on students' learning interests. This is evidenced by the results of the instrument validity test which amounted to 0.00. Meanwhile, it is said to be significant if the results of the instrument validity test <0.05. In this research hypothesis, Ho is rejected and Ha is accepted, so what is accepted is the research hypothesis Ha is accepted which has an effect of infrastructure on students' learning interests at the Amiruddiniyah Islamic Boarding School, Bandar Tinggi Village, Bilah Hulu District, Labuhanbatu Regency, North Sumatra. Keywords: infrastructure, student interest in learning